Coloniality of Power, Eurocentrism, and Latin America - Quijano, Anibal (Nepantla: Views from South, 2000)
What is termed globalization is the culmination of a process that began with the constitution of America and colonial/modern Eurocentered capitalism as a new global power. One of the fundamental axes of this model of power is the social classification of the world’s population around the idea of race, a mental construction that expresses the basic experience of colonial domination and pervades the more important dimensions of global power, including its specific rationality: Eurocentrism. The racial axis has a colonial origin and character, but it has proven to be more durable and stable than the colonialism in whose matrix it was established. Therefore, the model of power that is globally hegemonic today presupposes an element of coloniality. In what follows, my primary aim is to open up some of the theoretically necessary questions about the implications of coloniality of power regarding the history of Latin America.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé